Filsafat Cinta Jalaluddin Rumi dalam Upaya Mencegah Paham Radikalisme di Indonesia - Muhammad Farhan Kusnadi; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to determine the concept of Jalaluddin Rumi's philosophy of love, where this concept can be used as an effort to prevent radicalism in Indonesia. This type of research is qualitative research and the method used in this research is descriptive analysis study. Loving the country is the same as loving the universe as the concept of Jalaluddin Rumi's philosophy of love. This research concludes that instilling a sense of love for the country through sidelines of learning can protect students' minds from the dangers of radicalism.